2009
DOI: 10.1016/j.bej.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Biobleaching of high quality pulps with laccase mediator system: Influence of treatment time and oxygen supply

Abstract: In this study we examined the influence of the treatment time and addition of oxygen on the efficiency of a laccase mediator system (L) applied to flax pulp at atmospheric pressure. The redox potential and the dissolved oxygen concentration during L tests are measured. After L stage, an alkaline extraction (E) is carried out. The pulp properties (kappa number, brightness and viscosity) and the effluents properties (color and COD) were measured in order to evaluate the environmental impact of this enzymatic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 20 publications
(30 reference statements)
2
18
0
2
Order By: Relevance
“…When the AOX reduction was more than 0.14, the change in the rate of AOX reduction was small. This was similar to the results obtained in previous studies (Balakshin et al 2000(Balakshin et al , 2001aFillat and Roncero 2009), which revealed that the reaction of AOX reduction could be separated into two stages. In the initial stage, when the AOX reduction was less than 0.14, the lignin was degraded rapidly.…”
Section: Effect Of Aox Reduction On the Rate Of Aox Reductionsupporting
confidence: 82%
“…When the AOX reduction was more than 0.14, the change in the rate of AOX reduction was small. This was similar to the results obtained in previous studies (Balakshin et al 2000(Balakshin et al , 2001aFillat and Roncero 2009), which revealed that the reaction of AOX reduction could be separated into two stages. In the initial stage, when the AOX reduction was less than 0.14, the lignin was degraded rapidly.…”
Section: Effect Of Aox Reduction On the Rate Of Aox Reductionsupporting
confidence: 82%
“…The Po stage was performed in a hot, strongly alkaline medium, which may have resulted in modified cellulose being more markedly degraded than during the viscosity measurements. 33 Therefore, the viscosity differences between L and Po may have resulted from degradation of cellulose modified by the LMS. On the other hand, cellulose was probably not oxidized to carbonyl groups by the MtL.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, xylanase and laccase enzymes were reported to decolourise and detoxify the effluent generated by pulp and paper industry [1,2]. Both these enzymes have shown the ability to bleach kraft pulp [3,4] as well as to deink the recycled paper [5]. Application of xylanase and laccase together can considerably decrease the load of chemicals on environment caused by pulp and paper industry.…”
Section: Introductionmentioning
confidence: 98%